Pelatihan penjaminan mutu dan pembelajaran IPA dan Matematika berbasis STEM pada Kurikulum Merdeka dalam pengembangan Projek Penguatan Profil Pelajar Pancasila (P5) - Adi Rahmat; Aan Hasanah; Irma Rahma Suwarma; Rini Solihat; Tuszie Widhiyanti; Ratni Purwasih (IKIP SILIWANGI, 2024)
Commitment to the Society (PKM) is aimed at sustainable training of teachers and can be one of the solutions to improve the quality of standard content and learning processes. One is through quality assurance training and learning IPA and mathematics-based stem on an independent curriculum in developing a project to strengthen the profile of students' Pancasila (P5). This PKM partner is the head of the school and the teacher of the core subjects of IPA in some high schools in the district of Tasikmalaya. This dedication phase is FGD with science teachers on needs analysis, potential and problem analysis, strengthening and supporting training preparation, reinforcement and support training implementation, follow-up studies, evaluation and reporting preparation. The result of this dedication is that the participants of the STEM-based learning activities declare to gain knowledge and experience in STEM-based learning. After this training, the participants declared that they were ready to try to implement STEM-based learning in their respective schools.